The role of emotional intelligence on academic motivation of schoolchildren - Taibolatov, Kuandyk M.; Pfeyfer, Nellie E.; Burdina, Elena I.; Kudysheva, Ainash A.; Bolatov, Aidos K. (Frontiers in Education, 2024)
The purpose of this study was to inverstigate the relationship between emotional intelligence and academic motivation among secondary school students in Kazakhstan. In total, 682 schoolchildren in grades 6 to 8, corresponding to the 11/12-year Kazakhstani curriculum, were interviewed, and their level of emotional intelligence was analysed using a scale that assessed the level of interpersonal and intrapersonal emotional intelligence, understanding emotions, managing emotions, and general level of emotional intelligence. The results showed that emotional intelligence levels varied by class and gender, with males scoring higher on intrapersonal emotional intelligence, emotion management, and general emotional intelligence, while females scored higher on interpersonal emotional intelligence. Levels of academic motivation were also found to vary by grade and gender, with 6th grade students and females having higher levels of motivation. There was a significant positive correlation between emotional intelligence and academic motivation. Moreover, the study described differences in the level of emotional intelligence in the predominance of the academic motivation (intristic or extrinsic), desire to achieve success in school or avoid failure, and in the implementation of motives in the schoolchildren's behavior. Thus, this study indicates the relationship between the level of emotional intelligence and academic motivation of schoolchildren. The results of the study are important for policy makers in the field of school education and planning the academic life of schoolchildren.